Simultaneous Identification of Neutral and Anionic Species in Complex Mixtures without Separation - Zhao, Yanchuan; Chen, Lily; Swager, Timothy M. (Angewandte Chemie International Edition, 2016)
A chemosensory system is reported that operates without the need for separation techniques and is capable of identifying anions and structurally similar bioactive molecules. In this strategy, the coordination of analytes to a metal complex with an open binding cleft generates “static structures” on the NMR timescale. Unique signals are created by strategically placing fluorine atoms in close proximity to bound analytes so that small structural differences induce distinct 19F NMR shifts that can be used to identify each analyte. The utility of this method is illustrated by quantifying caffeine levels in coffee, by identifying ingredients in tea and energy drinks, and by discriminating between multiple biogenic amines with remote structural differences six carbon atoms away from the binding site. We further demonstrate the simultaneous identification of multiple neutral and anionic species in a complex mixture. Regular or decaf? A chemosensory system based on a complex with palladium (see picture, red semicircles) and a pincer ligand with fluorinated groups (blue) is reported. The system operates without need of separation techniques and is capable of identifying multiple structurally similar analytes such as caffeine in complex mixtures by 19F NMR spectroscopy. Neutral and anionic species are simultaneously detected by this method.